Structural elucidation of the binary mixtures of [emim][bf4] and [bmim][bf4] in ethyl-substituted solvents by isothermal titration calorimeter. - Jain, Preeti (ChemistrySelect, 2018)
In order to address the issue whether both ionic liquids and solvents influence the enthalpy of their solutions, highly accurate excess partial molar enthalpy, urn:x-wiley:23656549:media:slct201800976:slct201800976-math-0001 values have been measured using Isothermal Titration Calorimeter (ITC). Therefore, thermodynamic behavior has been observed in the mixtures containing ionic liquids. It essentially depends on the molecular structure of the constituents of the mixture. The hydrogen bonding between ionic liquids and ethyl‐substituted solvents (2‐ethoxyethanol, ethylene glycol, diethylamine, ethyl acetate and N,N‐ diethylacetamide) may lead to strong ion‐solvent interactions. In the present study, an effort has been made to quantify various interactions between ionic liquid and solvent, based on the urn:x-wiley:23656549:media:slct201800976:slct201800976-math-0002 values. Linear solvation free relation shows dependence of limiting excess partial molar enthalpies, urn:x-wiley:23656549:media:slct201800976:slct201800976-math-0003 upon the solvent properties. Structural orientation of solvent molecules and ionic liquids also described by the urn:x-wiley:23656549:media:slct201800976:slct201800976-math-0004 values. The ion‐ion, ion‐solvent interactions have also been investigated in terms of the enthalpic interaction parameters, urn:x-wiley:23656549:media:slct201800976:slct201800976-math-0005 and relative apparent molar enthalpy, φL of ionic liquid‐ethyl‐substituted solvent systems.